Intergenerational solidarity in a developing welfare state: The case of South Korea - Martin Gurín; Martina Brandt (International Journal of Social Welfare, 2024)
With our analysis of the Korean society we intend to make an innovative contribution to research on intergenerational solidarity by examining how the introduction of welfare policies has changed patterns of intergenerational solidarity. Using aggregated data from the Korean Longitudinal Study of Aging, the Korean General Social Survey, and the Korean Social Survey, we examine the changing character of intergenerational solidarity by focusing on national trends in both societal practice and intergenerational norms from 2002 to 2018. Our findings show that patterns of Korean intergenerational solidarity have modified in various respects. The normative dimension of the familial/filial contract has profoundly changed along with the developing welfare state, shifting from a dominantly filial piety-centric character to more complementarity contract-based norms in which children, welfare state and society are all assigned responsibility for the well-being of parents. Intergenerational "functional" solidarity, however, in terms of the exchange of money and practical support has not de-filialized.
Keywords: 330; intergenerational solidarity; population aging; societal change; South Korea; welfare state